Highly Sensitive and Selective Copper (II)-Catalyzed Dual-DNAzyme Colorimetric Biosensor Based on Exonuclease III-Mediated Cyclical Assembly - Baiqiang Zhai (MDPI AG, 2021)
“Cu-DNAzyme” and “G4-DNAzyme” were used to develop a “turn-off” dual-DNAzyme colorimetric biosensor, which could be used to detect Cu2+ by employing exonuclease III-mediated cyclical assembly (EMCA). EMCA was based on the cleavage activity of Cu2+ to transfer the linkage sequences of the substrate strand and enzyme strand into the transition sequence. The horseradish peroxidase (HRP)-mimicking activity of the G4-DNAzyme was lost after binding with the complementary transition sequence and was hydrolyzed by Exo III. These results demonstrate that the proposed colorimetric biosensor was an effective method for ultradetection of trace metals in a high original signal background. Due to the high sensitivity of the biosensor, the limit of detection (LOD) of Cu2+ is 0.16 nM. This design offers a general purpose platform that could be applied for the detection of any metal ion target through adjustment of metal-dependent DNA-cleaving DNAzymes, which is of great significance for the rapid determination of food safety.